Changes in the avascular area of the meniscus using mesenchymal stem cells and growth plate chondrocytes in a pig model. Issue 6 (13th July 2021) - Tomaszewski, Ryszard; Rost‐Roszkowska, Magdalena; Wilczek, Grażyna; Gap, Artur; Wiktor, Łukasz
Abstract: Menisci are wedge‐shaped cartilage discs that are divided into two parts: the avascular and vascular regions. They are formed by fibrocartilage tissue, which contains round cartilage‐like cells and extracellular matrix. Meniscus injury in animals is a common orthopedic problem, but data on the natural healing process mainly deals with the vascular zone. The healing processes in the avascular zone of the meniscus are significantly limited. Thus, this study aimed to evaluate autologous growth plate chondrocytes' impact on the healing process of a damaged meniscus in the avascular zone based on a growing animal model. The study group consisted of 10 pigs at about three months of age. From each animal, chondrocytes from the iliac growth plate and from concentrated bone marrow were taken. Knee joints were divided into right (R) and left (L). The medial meniscus of the R knee joint was treated with a hyaluronic acid based scaffold incubated with bone marrow cells from marrow aspirates (nCHON ). The medial meniscus of the L knee joint was treated with a hyaluronic acid based scaffold incubated with bone marrow cells from marrow aspirates supplemented with immature chondrocytes isolated from growth plates (wCHON ). The meniscus was damaged in the avascular zone in both knee joints. Followingly, the damaged part of the meniscus was filled with a scaffold with cells from the concentrated bone marrow and from growth plate chondrocytes. In the control group, a scaffold with concentrated bone marrow cells was used. After three months the animals were euthanized and preparations (microscopic slides) were made from the meniscus' damaged part. A qualitative and quantitative analysis have been prepared. The wCHON group in comparison with the nCHON group showed a statistically significantly higher number of fusiform cells on the surface of the graft as well as better healing of the graft. In addition, the degree of vascularization was higher in specimens from the wCHON group than in the nCHON group. The results of our research on immature pig knees revealed that mesenchymal stem cell and growth plate chondrocytes could be treated as the cell source for meniscus reconstruction, and growth plate chondrocytes enhance healing processes in the avascular zone of the injured meniscus. Abstract : The study aimed to evaluate autologous growth plate chondrocytes' impact on the healing process of a damaged meniscus in the avascular zone based on a growing animal model. The study group consisted of 10 pigs at about three months of age. From each animal, chondrocytes from the iliac growth plate and from concentrated bone marrow were taken. The medial meniscus of the right knee joint was treated with a hyaluronic acid based scaffold incubated with bone marrow cells from marrow aspirates (nCHON). The medial meniscus of the left knee joint was treated with a hyaluronic acid‐based scaffold incubated with bone marrow cells from marrow aspirates supplemented with immature chondrocytes isolated from growth plates (wCHON). The meniscus was damaged in the avascular zone in both knee joints. The damaged part of the meniscus was filled with a scaffold with cells from the concentrated bone marrow and from growth plate chondrocytes. In the control group, a scaffold with concentrated bone marrow cells was used. After three months a qualitative and quantitative analysis have been prepared. The results showed that (1) MSCs and growth plate chondrocytes are a useful cell source for meniscus reconstruction, (2) growth plate chondrocytes enhancehealing processes in the avascular zone of the injured meniscus, (3) meniscus injury is becoming more common even in pediatric patients and can lead to several joint injuries of the knee, especially degenerative changes.